The dragon prince. [1], Through the moon - Ehasz, Aaron; Ehasz, Aaron; Wartman, Peter; Richmond, Justin; Richmond, Justin (Dragon Prince., 2020)
"The Dragon Prince has been reuinted with his mother, the Human Kingdoms, and Xadia are at peace, and humans and elves are ready to move on. Only Rayla is still restless. Unable to believe Lord Viren is truly dead, and haunted by questions about the fate of her parents and Runaan, she remains trapped between hope and fear. When an ancient ritual calls her, Callum, and Exran to the Moon Nexus, she learns the lake is a portal to a world between life and death. Rayla seizes the opportunity for closure--and the chance to confirm that Lord Viren is gone for good. But the portal is unstable, and the ancient Moonshadow elves who destroyed it never intended for the portal to be reopened. Will Rayla's quest to uncover the secrets of the dead put her living friends in mortal danger?"--Provided by publisher